2009
DOI: 10.1084/jem.20092176
|View full text |Cite
|
Sign up to set email alerts
|

Nfil3/E4bp4 is required for the development and maturation of NK cells in vivo

Abstract: Nuclear factor interleukin-3 (Nfil3; also known as E4-binding protein 4) is a basic region leucine zipper transcription factor that has antiapoptotic activity in vitro under conditions of growth factor withdrawal. To study the role of Nfil3 in vivo, we generated gene-targeted Nfil3-deficient (Nfil3−/−) mice. Nfil3−/− mice were born at normal Mendelian frequency and were grossly normal and fertile. Although numbers of T cells, B cells, and natural killer (NK) T cells were normal in Nfil3−/− mice, a specific dis… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

13
269
1

Year Published

2011
2011
2024
2024

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 293 publications
(288 citation statements)
references
References 33 publications
13
269
1
Order By: Relevance
“…5B). Because NK cells are absent in the NFIL3-deficient mice (30,46), it is important to note that these experiments do not necessarily indicate that the increase in IL-12p40 alone is the cause of disease in these mice. Further experiments with conditional Nfil3 knockout mice will be necessary to establish the cell-specific contributions of NFIL3 to the overall immune response to T. gondii.…”
Section: Analysis Of Il-10-induced Transcription Factors Narrows the mentioning
confidence: 99%
“…5B). Because NK cells are absent in the NFIL3-deficient mice (30,46), it is important to note that these experiments do not necessarily indicate that the increase in IL-12p40 alone is the cause of disease in these mice. Further experiments with conditional Nfil3 knockout mice will be necessary to establish the cell-specific contributions of NFIL3 to the overall immune response to T. gondii.…”
Section: Analysis Of Il-10-induced Transcription Factors Narrows the mentioning
confidence: 99%
“…Developmental and survival signals downstream of the IL-15 receptor (IL-15R) in NK cells are thought to be mediated, in part, by the basic leucine zipper transcription factor (TF) Nfil3 (nuclear factor interleukin-3 regulated; also known as E4BP4) (10,11). However, whereas expression of Nfil3 is essential for early development of NK cells, survival and homeostasis of mature NK cells is Nfil3 independent (12).…”
Section: T-box Transcription Factormentioning
confidence: 99%
“…In E4bp4 knockout mice, it has been shown that E4BP4 is critical for NK cell development and IgE expression in B cells (12)(13)(14). In addition to its role in the immune system, E4bp4 is also highly expressed in the liver, adipose tissue, and the suprachiasmatic nuclei of the hypothalamus (15).…”
mentioning
confidence: 99%